2018
DOI: 10.1111/rda.13200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various levels of dissolved oxygen on reactive oxygen species and cryocapacitation‐like changes in bull sperm

Abstract: The present investigation was carried out to study the effect of various levels of dissolved oxygen (DO) on reactive oxygen species (ROS) and cryocapacitation-like changes in bull sperm. Egg yolk-Tris-glycerol (EYTG) extender was split into four subextenders; viz., Extender I (control; no flushing with liquid nitrogen (LN )), Extender II, Extender III and Extender IV were flushed with LN for 40, 16 and 8 min, respectively. The DO levels were standardized to 11.7, 2, 4 and 8 ppm, respectively, in control (Exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…Experts have developed media for sperm survival during the cooling and freezing techniques [15]. Many challenges, such as media toxicity [52], irregular pH [53], ROS [54], energy source [55], sperm membrane damage [24], and cryo-shock preservatives [56], were faced and have been resolved. Extenders protect sperm, conserve motility, and fertility over time by stabilizing the plasmalemma, provide energy substrates, and prevent harmful effects of pH and osmolarity changes [57].…”
Section: Development Of Semen Extendermentioning
confidence: 99%
“…Experts have developed media for sperm survival during the cooling and freezing techniques [15]. Many challenges, such as media toxicity [52], irregular pH [53], ROS [54], energy source [55], sperm membrane damage [24], and cryo-shock preservatives [56], were faced and have been resolved. Extenders protect sperm, conserve motility, and fertility over time by stabilizing the plasmalemma, provide energy substrates, and prevent harmful effects of pH and osmolarity changes [57].…”
Section: Development Of Semen Extendermentioning
confidence: 99%
“…Three different approaches have been used i.e. flash frozenthaw process using liquid nitrogen, nitrogen gas bubbling/ gassing process (2-3 bubbles per second) using gaseous nitrogen and applying negative pressure to the flask containing diluent with the help of modified vacuum pump (Pande et al, 2015;Mustapha et al, 2017;Amin et al, 2018;Balamurugan et al, 2018;Kumar et al, 2018). Further refinement of DO level was indicated in nitrogen gassing method as a gap between the 4 ppm and 8 ppm existed.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive supercooling during the process of freezing results in a rapid ice formation, with the possibility of physical damage resulting in significant deteriorations in seminal parameters, exaggerated by the supra-physiological level of free radicals. Various studies have indicated that male germ cells at various stages of its differentiation (Agarwal and Said, 2003) and through interaction between spermatozoa and dissolved oxygen in extender (Amin et al 2018;Lone, 2018) have the potential to generate reactive oxygen species (ROS) and reactive nitrogen species (RNS). The ROS include singlet oxygen ( 1 O 2 ), hydrogen peroxide (H 2 O 2 ), superoxide anion (O 2 -) and hydroxyl radicals (OH -) (Lone et al 2018), likewise, RNS include nitrogen dioxide (NO 2 ), peroxynitrite (ONOO -) and nitric oxide (NO) (Nash et al 2012), which have been recently implicated in inducing poor sperm function and sperm fertilizing ability in bovines.…”
Section: Introductionmentioning
confidence: 99%